Rise of Love and the People: French Matter and Manner in the Early Victorian Drama of Edward Bulwer-Lytton - Ana Fernández-Caparrós Turina (Cahiers Victoriens et Edouardiens)
In the short period between 1837, when Queen Victoria came to the throne, and 1843, when the Theatre Regulation Act amended the Licensing Act of 1737 and thus reconfigured theatrical freedom and production in the United Kingdom, the fruitful collaboration of renowned novelist Edward Bulwer-Lytton and actor and theatrical manager William Charles Macready would prove to be decisive in shaping early Victorian drama and setting high standards in production and artistic integrity, which would be followed by successive managers. Both in the pursuit of the theatrical reforms that were advocated by Bulwer as a Whig member of parliament and in his new venture into dramatic writing, the author relied heavily on French models. The article analyses the French influence in Bulwer’s first dramas that composed his cycle of French history plays, The Duchess de la Vallière (1837), The Lady of Lyons, or Love and Pride (1838) and Richelieu, or The Conspiracy (1839). Beyond using French sources and setting the action of these plays in France, the inspiration from French culture and history crucially imbued Bulwer with a sense of freedom to essay his peculiar and intuitive conflation of politics and romance. This freedom is especially the case in Bulwer’s first works, for which after the revolutionary experience, a French context became the most suitable framework to articulate liberal ideas, to reflect the creation of a modern consciousness that was represented by the rise of the people and to connect these interests with the theatrical portrayal of manners, passion and sentiment.